Implication of the endogenous midgut microbiota on cell genotoxicity and biological fitness of Culex pipiens complex (Diptera: Culicidae) - Alaa Fouaad; Nagwa A. Rashdan; Refaat M. Gabre; Emtithal M. Abdel-Samie (Journal of Basic and Applied Zoology)
Abstract Background Culex pipiens is one of the most important mosquito transmitter of diseases that attains its greatest impact as a vector through spreading out several serious arboviral, protozoal and filarial diseases. Furthermore, it is a native in Europe, Asia and Africa. Results The current study aimed to find a new mosquito biocontrol agents through using the isolated endogenous midgut microbiota, Atlantibacter hermannii, Klebsiella sp. and Enterobacter cloacae, that were isolated from Culex pipiens complex females’ gut. The genotoxical effect of the isolated bacteria was estimated through using alkaline comet assay and related to the impact on mosquito longevity and reproductive potential that might be observed. A distinguish increase in cell DNA damage accompanied with an outstanding effect on life span and reproductive fitness was clear in case of vectors under investigation. Conclusions Data in this research suggest the use of the endogenous bacteria as a potential control techniques that could be integrated in to the environmentally friendly mosquito control strategies.